2019
DOI: 10.3748/wjg.v25.i3.287
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Na+/Ca2+exchanger 1 in digestive system physiology and pathophysiology

Abstract: The Na+/Ca2+ exchanger (NCX) protein family is a part of the cation/Ca2+ exchanger superfamily and participates in the regulation of cellular Ca2+ homeostasis. NCX1, the most important subtype in the NCX family, is expressed widely in various organs and tissues in mammals and plays an especially important role in the physiological and pathological processes of nerves and the cardiovascular system. In the past few years, the function of NCX1 in the digestive system has received increasing attention; NCX1 not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 106 publications
0
15
0
Order By: Relevance
“…Intestinal basal epithelial cells of small intestine, colon and rectum express Ncx1. Previous reports have shown that Vitamin D enhances Ncx1 gene expression and regulates transmembrane Ca 2+ transport (Liao et al, 2019). In duodenal mucosal epithelium, bicarbonate secretion was regulated by Ncx1 reverse mode activation (Dong et al, 2005).…”
Section: Effects Of Gyp On Protein Expression and Glp-1 Stainingmentioning
confidence: 85%
“…Intestinal basal epithelial cells of small intestine, colon and rectum express Ncx1. Previous reports have shown that Vitamin D enhances Ncx1 gene expression and regulates transmembrane Ca 2+ transport (Liao et al, 2019). In duodenal mucosal epithelium, bicarbonate secretion was regulated by Ncx1 reverse mode activation (Dong et al, 2005).…”
Section: Effects Of Gyp On Protein Expression and Glp-1 Stainingmentioning
confidence: 85%
“…The sodium-calcium exchanger (NCX) is a membrane protein within the solute carrier family 8 (SLC8) (Khananshvili, 2013). In humans, the NCX family is involved in cellular Ca 2+ homeostasis in the intestine, heart, skeletal muscle and nervous system (Loffing et al, 2001;On et al, 2008;Khananshvili, 2013;Liao et al, 2019). Currently, three NCX exchangers have been implicated in Ca 2+ transport, NCX1, NCX2 and NCX3 (Khananshvili, 2013).…”
Section: Sodium-calcium Exchangers (Ncx)mentioning
confidence: 99%
“…NCX was previously reported to be expressed in small intestinal epithelial cells and to function in the forward mode that is involved in the absorption of Ca 2+ into the bloodstream. However, NCX also has a role in GI epithelial anion secretion (125).…”
Section: Ncxmentioning
confidence: 99%